PDCT-22. GENOME-WIDE DISCOVERY OF NOVEL SUSCEPTIBILITY POLYMORPHISMS FOR TREATMENT-ASSOCIATED HYPOTHYROIDISM IN PEDIATRIC MEDULLOBLASTOMA. (6th November 2017) - Brown, Austin; Bielamowicz, Kevin; Sonabend, Rona; Scheurer, Michael; Lupo, Philip; Paulino, Arnold; Dreyer, Zoann; Mahajan, Anita; Chintagumpala, Murali; Okcu, M Fatih
Abstract: Pediatric medulloblastoma patients are at high risk of developing hypothyroidism after craniospinal radiotherapy (CSI). We investigated the role of genetic variation on hypothyroidism susceptibility in children and adolescents with medullobastoma. METHODS: We reviewed the medical records in 61 medulloblastoma patients treated at Texas Children's Hospital between 1997 and 2013 who completed baseline and yearly follow-up thyroid function tests. Genome-wide genotyping was performed on Illumina HumanOmni1 and HumanOmni2.5 BeadChip single nucleotide polymorphism (SNP) arrays. Following standard quality control measures and exclusion of rare variants (minor allele frequency [MAF] <5%), 572, 562 autosomal SNPs were included in our analyses. The association between each SNP and hypothyroidism was tested using Fisher's exact test and logistic regression, assuming additive allelic effects. RESULTS: A total of 25 patients (41%) developed hypothyroidism over a median follow-up of 8.3 years from diagnosis (range: 1.8-17.2 years). Primary hypothyroidism was identified in 9 (36%) cases, while the remaining 16 (64%) cases developed central hypothyroidism. Hypothyroidism was detected in 13 of 40 (33%) individuals exposed to <30 Gy CSI and 12 of 21 (57%) individuals exposed to ≥30 Gy CSI (p=0.06). Genome-wide association analysis identified several risk loci, including 3 variants associated with hypothyroidism (p-value<1x10 -5 ) at chromosome 2q11.2 ( NPAS2 gene). The top overall SNP (MAF=27.5%, p-value=6.5x10 -7 ) remained strongly associated with hypothyroidism after accounting for possible confounders, including CSI dose, CSI type (proton/photon), age, sex, and genetic ancestry. CONCLUSIONS: While these results require replication in an independent population, the preliminary findings suggest susceptibility to treatment-related hypothyroidism is strongly influenced by a common genetic variation in NPAS2 . The NPAS2 gene, a central component of the circadian rhythm network, is a transcriptional activator and regulator of DNA damage response and DNA repair genes. Once validated screening strategies for hypothyroidism can be modified based on genetic susceptibility in patients receiving radiotherapy including the thyroid gland.